Co-oxidation of octane and benzaldehyde using molecular oxygen with Au–Pd/carbon prepared by sol-immobilisation1. Issue 8 (21st August 2015) - Peneau, Virginie; Shaw, Greg; Freakley, Simon J.; Forde, Michael M.; Dimitratos, Nikolaos; Jenkins, Robert L.; Taylor, Stuart H.; Hutchings, Graham J.
<x xml:space="preserve">Abstract</x> Oxidation of octane in the presence of benzaldehyde over a AuPd catalysts leads to the formation of octyl benzoate.